A Study On Chemical Management In A Tire Manufacturing Industry - Sabri, Farhimie (Progress in Engineering Application and Technology, 2023)
Chemical Management is a safe process in the supply chain that requires adequate protection of workers and the environment through proper care in the delivery, use, storage and disposal of chemicals. If the safety practices that have been established in the Chemical Management are not used or practiced in the daily work process, various accidents or injuries may occur to employees. The use of chemicals in tire production in large quantities if not controlled in terms of handling and storage may lead to unexpected accidents. Because of that, there is chemical management training was given to workers involved in the handling and storage of chemicals in the factory. Questions was given in the form of Pre and Post which have to be answered by employees via online. Statistical Package for the Social Science (SPSS) was used to analyze the data obtained based on the survey questions. The results obtained were that the training provided achieves good effectiveness. The importance of this study is to provide a way how to improve the safety and health of workers who are exposed to dangerous chemicals. This study can also provide new knowledge to employees about the importance of chemical management for work processes involving chemicals in order to improve safety in the workplace.